A review on perfluoroalkyl acids studies: Environmental behaviors, toxic effects, and ecological and health risks - Wenxiu Liu (Taylor & Francis Group, 2019)
Perfluoroalkyl acids (PFAAs) are emerging persistent organic pollutants that are globally distributed in the environment. In the present review, the occurrence of PFAAs and their behavior in aquatic ecosystem were summarized, and the health and ecological risk assessment and the multimedia fate simulation were investigated. PFAAs are most likely to exist in the aqueous phase, and PFAAs in atmosphere are also able to enter water bodies through diffusion and wet and dry deposition and eventually become widely distributed in various environmental media. The air-solid partition is considered to be one of the major factors in the long-distance transportation of the pollutants. The pKa values and organic carbon fraction of the sediment could influence the partition of PFAAs between water and sediment. Otherwise, PFAAs have teratogenic, mutagenic and other toxic effects and they could be accumulated by biota, and magnified through trophic level. The ecological and health risks of PFOA and PFOS were assessment. In order to explore the partition mechanism and reduce the uncertainty of the simulation of the transport, transformation and fate, the experimental methods on physicochemical properties of PFAAs should be developed. Moreover, further studies on toxicities of PFAAs are necessary for health and ecological risk assessment.